National Medicine Exam: an Analysis of the last decade of theoretical exams in peruvian last year medical students - Mendoza Chuctaya, Giuston (2021)
Objectives: To assess grades from the National Medical Exam (ENAM, according to its Spanish initials) that serve to last year medical students as a prerequisite to apply for places in Peruvian Medical Rural Service (SERUMS, according to its Spanish initials) between 2009 and 2019. Materials and Methods: This is an analytical retrospective study where a secondary analysis of registries for applying to the Peruvian Medical Rural Service (SERUMS) between years 2009 and 2019. Number of applicants to SERUMS places were determined, together with median values of ENAM results. Each of these pieces of information were presented according to different characteristics. Bivariate and multivariate models were used for obtaining prevalence rates. Results: More than thirty thousand students were assessed (30750), and 9087, 17607, and 4056 were from public, private, and foreign medical schools, respectively. Forty-three percent of those who registered tor applying the SERUMS failed the exam. Percentages of those who failed were 31%, 34%, and 79% of those coming from public, private, and foreign medical schools, respectively. Multivariate analyses showed that those who most frequently failed came from private medical schools (odds ratio [OR]: 1.42; 95% CI: 1.37–1.47, p<0.001), those who studied medicine in a Lima City medical school (OR: 1.18; 95% CI: 1.14 – 1.22, p<0.001), and those who studied outside Peru.  Conclusions: There is a greater number of physicians doing rural service (SERUMS), but many of them fail the examination (ENAM), particularly those coming from private medical schools in Lima City and those who come from foreign medical schools. These results suggest that a great proportion of physicians applying for the rural service are not adequately qualified, at least in the theoretical areas which are measured by the ENAM.